A Comparative Study of Knowledge, Attitude, and Practice of Technicians and Their Supervision of Public and Dental Clinics in Mashhad: A Cross-Sectional Study - Javad Sarabadani; mahnaz fazaeli; kiarash ghazvini; ali labafchi; Sedighe Karbasi; armaghan salehi; Abdollah Javan (Mashhad University of Medical Sciences, 2021)
Introduction: This study aimed to compare the knowledge, attitude, and practice of the technicians and their supervision of dental clinics in Mashhad. Materials and Methods: In this study, the researchers examined 84 clinics and distributed the questionnaire among the technicians. The quality of the sterilization was evaluated by biological and chemical indicators and the results of the questionnaire. The biological and chemical indicators were placed inside the autoclave. The questionnaire investigated the incubation method, autoclave numbers, device performance monitoring method, indicator type, device temperature and pressure, and the number of times the device was turned on during the day, as well as the knowledge, attitude, and performance of the technicians. The collected data were analyzed in SPSS software (version 19). Results: Based on the findings, class B autoclaves were used in only 59% of the clinics. It was revealed that 7%, 26%, and 31% of the clinics applied biological testing, chemical testing, and physical methods to assess autoclave performance, respectively. The results of biological tests were positive in 20% of clinics, and 11.9% of chemical indicators did not show sufficient color change. It was also found out the knowledge, attitude, and performance scores were significantly higher in the dental technicians than those in the physician technicians. Conclusion: According to the results of this study, it is recommended that the technicians of the dental department of public clinics be dentists as well. Public clinics should pay more attention to the quality of sterilization and infection control. The improvement of the technicians' knowledge will lead to better performance and consequently to an increase in the quality of sterilization and infection control.